2010
DOI: 10.1002/clen.201000131
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Determination and Pollution of the Soil and Plants of Southeast Tavşanlı (Kütahya, Turkey)

Abstract: The investigation area is located to the east of Kütahya-Tavşanlı and, covers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 22 publications
1
15
2
Order By: Relevance
“…Food crops may accumulate metal concentrations in their bodies when available to them [9,10]. Food chain is the main source of human exposure to metal contaminations [2,5]. These MTF values were found lower than those reported by Jan et al [5] and Muchuweti et al [9].…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Food crops may accumulate metal concentrations in their bodies when available to them [9,10]. Food chain is the main source of human exposure to metal contaminations [2,5]. These MTF values were found lower than those reported by Jan et al [5] and Muchuweti et al [9].…”
Section: Discussionmentioning
confidence: 49%
“…Oral reference dose for Zn, Cu, and Fe are 3.0EÀ1, 4.0EÀ2, and 3.0EÀ1 mg/kg per day, respectively [2]:…”
Section: Hrimentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metal pollutants have been considered to be one of the most critical global pollutants and pose a serious threat to human health and natural ecosystems (Lotze et al 2006;Li et al 2007;Li et al 2009;Fang et al 2009;Arik and Yaldiz 2010;Deng et al 2010;Naser 2013;Zhang et al 2009b). The first national soil pollution status survey bulletin released on April 17, 2014 launched by the Ministry of Environmental Protection and Ministry of Land and Resources of the People's Republic of China demonstrated that the ratio of exceeding soil standards in all of the samples is 16.1 % and the rate of arable land reaches 19.4 %, while the ratio of Cd is 7.0 % in all of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Increased inputs of these elements in aquatic and terrestrial environments have led to serious environmental pollution. As with human-induced mobilization of trace elements into the biosphere (Arık and Yaldız 2010;Vural 2014;Baslar et al 2009), mobilization of elements in the alteration areas is also an outstanding process in the geochemical cycling of these elements (Vural 2014). Alteration of the rocks reduces the pH of the environment and so makes most elements mobilize.…”
Section: Introductionmentioning
confidence: 99%